The Influence of the Chanting of Qur'an Verses By Birth Attendant Against Decreased Anxiety In Mothers Maternity: An Intervention Effectiveness Study Spiritual - Nurasiah, Ai; Haendrayani, Nanay (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Childbirth is a special moment in a woman's life. However, this process often presents various physical and psychological challenges, especially when entering the active phase of childbirth. Therapy in the form of chanting verses of the Qur'an carried out by delivery companions is one of the non-pharmacological methods that is believed to be able to provide a sense of calm and reduce Anxiety. This study aims to evaluate the effectiveness of Qur'anic chanting therapy by childbirth assistants in lowering the level of Anxiety in maternity mothers at PONED UPTD Luragung Health Center, Kuningan Regency. Methods: This study is a quantitative study with a pre-experimental design. The research design used is a group Pretest[1]Posttest Design. The research sample was taken using an accidental sampling technique, with 20 respondents giving birth from April to May 2024. The instrument used was a questionnaire to measure anxiety levels. Data analysis was carried out using a t-test to compare the level of Anxiety before and after the intervention in the form of chanting Qur'an verses by the delivery companion. The recitation of Qur'an verses is carried out based on the ability of each birth companion. Results: The results of the study showed that before being given the recitation of Qur'an verses, the majority of respondents experienced a level of severe Anxiety, which was as many as 15 people (75%). After the intervention, most of the respondents experienced a decrease in Anxiety into the mild anxiety category, which was as many as nine people (45%). Data analysis with paired sample t-test showed a t-count value of 5.304 with a p-value of 0.001 (p-value < 0.05), which indicates a significant difference in anxiety levels before and after being given the recitation of Qur'anic verses. Conclusion: The chanting of Qur'an verses by delivery assistants has been proven to be effective in reducing the level of Anxiety in maternity mothers at the PONED UPTD Luragung Health Center, Kuningan Regency. Therefore, the integration of spiritual aspects in childbirth services is very important to be carried out. This can help create services that are more meaningful, humane, and in accordance with the needs and values embraced by the community